The Lifebox Surgical Headlight Project: engineering, testing, and field assessment in a resource-constrained setting. Issue 13 (27th June 2020) - Starr, N; Panda, N; Johansen, E W; Forrester, J A; Wayessa, E; Rebollo, D; August, A; Fernandez, K; Bitew, S; Mammo, T Negussie; Weiser, T G
Abstract: Background: Poor surgical lighting represents a major patient safety issue in low-income countries. This study evaluated device performance and undertook field assessment of high-quality headlights in Ethiopia to identify critical attributes that might improve safety and encourage local use. Methods: Following an open call for submissions (December 2018 to January 2019), medical and technical (non-medical) headlights were identified for controlled specification testing on 14 prespecified parameters related to light quality/intensity, mounting and battery performance, including standardized illuminance measurements over time. The five highest-performing devices (differential illumination, colour rendering, spot size, mounting and battery duration) were distributed to eight Ethiopian surgeons working in resource-constrained facilities. Surgeons evaluated the devices in operating rooms, and in a comparative session rated each headlight in terms of performance and willingness to purchase. Results: Of 25 submissions, eight headlights (6 surgical and 2 technical) met the criteria for full specification testing. Scores ranged from 8 to 12 (of 14), with differential performance in lighting, mounting and battery domains. Only two headlights met the illuminance parameters of more than 35 000 lux during initial testing, and no headlight satisfied all minimum specifications. Of the five headlights evaluated in Ethiopia, daily operation logbooks noted variability in surgeons' opinions of lighting quality (6–92 per cent) and spot size (0–92 per cent). Qualitative interviews also yielded important feedback, including preference for easy transport. Surgeons sought high quality with price sensitivity (using out-of-pocket funds) and identified the least expensive but high-functioning device as their first choice. Conclusion: No device satisfied all the predetermined specifications, and large price discrepancies were critical factors leading surgeons' choices. The favoured device is undergoing modification by the manufacturer based on design feedback so an affordable, high-quality surgical headlight crafted specifically for the needs of resource-constrained settings can be used to improve surgical safety. Graphical Abstract: Poor surgical lighting represents a major patient safety issue in low-income countries, and currently there is no fit-for-purpose surgical headlight to meet the demands of this setting, both in terms of design and price. In this study, engineering testing of 14 surgical headlights, and field testing of five finalist candidate headlights with surgeons in Ethiopia, was undertaken to determine the best performing light and evaluate critical attributes for further design modifications. After testing in operating room working conditions and a head-to-head comparison test, one headlight was chosen that best fit design and cost preferences; this headlight will undergo further design modifications and testing to develop a final product for wide distribution and improvement of surgical safety. Bring the light